The Effect of Seed Pre-treatments on Germination indices and vegetative traits of Capparis mucronifolia Boiss in Laboratory and Greenhouse - Mahmood Abadeh; Malihe Sadeghi Bahmani; hamed hasanzadeh khankahdani; Maryam yektankhodaei (علوم و فناوری بذر ایران)
This experiment was conducted as a factorial based on a completely randomized design with four replications and the first factor was Culture medium with two levels: laboratory and Greenhouse, and the second factor was seed pre-treatment with five levels: Control, Leaching for 12 hours, Leaching for 12 hours and Soaking in gibberellic acid for 12 hours, Scarification with sandpaper and Scarification with sandpaper and Soaking in gibberellic acid for 12 hours. The results showed that in Greenhouse vegetative traits of plumule length (78.6 mm), radicle length (109.34 mm), seedling dry weight (102.7 mg), allometric coefficient (0.72) and seedling vigour (95) were higher than the laboratory (p<0.05). The results also showed that leaching and soaking in gibberellic acid pre-treatment increased indices and traits germination rate (5.56), mean daily germination (1.9), peak value (2.48), germination value (6.1), plumule length (61.9 mm), radicle length (86.1 mm), seedling dry weight (82.2 mg) and seedling vigour (94.3) (p<0.05). This pre-treatment also reduced day to beginning germination index (5.6) (p<0.05). The results of mean comparison of the interaction effect of Culture medium and Pre-treatment showed that in Greenhouse leaching and soaking in gibberellic acid pre-treatment reduced day to beginning germination index (4.2) and increased vegetative traits of plumule length (93 mm), radicle length (129.2mm), seedling dry weight (120.8 mg) and seedling vigour (124.9) (p<0.05).